Representaciones populares de la vida urbana: ciudad de México, 1890-1930 - Cornejo, Tomás (El Colegio de México, A.C., 2016)
In dialogue with the primary perspectives that have been developed to address the modernization of Latin America’s cities, this article addresses the vision of Mexico City’s urban working class as represented in the broadsheets reprinting the lyrics of popular corridos, which consistuted a tremendously rich cultural phenomenon. By examining the widespread production of these broadsheets throughout the bulk of the Porfirato up through the post-revolutionary period, this article contributes to an understanding of the working class’s experience of living in the capital. Three topics dealt with in the corridos are analyzed: housing problems, neighborhood social relations and changes in gender dynamics as a consequence of the precarity of family income in the new urban enviroment.